Regulation of the Switchable Luminescence of Tridentate Platinum(II) Complexes by Photoisomerization - Li, Yongguang; Fei, Yuexuan; Sun, Hongcheng; Yu, Shuangjiang; Liu, Junqiu (Frontiers in Chemistry, 2021)
Organoplatinum(II) complexes are promising candidate to construct smart supramolecular materials due to their unique flat structures. This prompt the molecules to aggregate induced by external stimuli, accompanying with intriguing luminescent properties. Nevertheless, the utilization of photo-responsive subunits to modulate their assemble behaviors and functions are still rarely explored. In this work, azobenzene(azo)-appended tridentate platinum(II) complexes with different linkers have been designed and synthesized. The intermolecular hydrogen bonding, π-π stacking and metal-metal interactions were finely controlled through the tiny alteration of the linkers, which was found to play vital role in self-assembly, photophysical and photoisomerization properties. Some of them exhibited dual emission bands originated from metal-perturbed triplet intraligand (3IL) and metal-metal to ligand charge transfer (3MMLCT) excited states due to the different intermolecular interactions. Based on this, the manipulation of switchable luminescence as well as the controllable morphologies has been realized by photoisomerization.